Temporospatial Control of Graphene Wettability. Issue 4 (30th November 2015) - Vijayarangamuthu, Kalimuthu; Ahn, Seungbae; Seo, Hyungtak; Yoon, Sang‐Hee; Park, Cheol‐Min; Jeon, Ki‐Joon
Abstract : The reversible migration of adatoms along a basal plane of graphene under electrical bias is experimentally demonstrated. Single‐layer graphene oxide with partial oxygen adatom coverage is utilized for this demonstration. The intensity ratio of G and G′ Raman modes is used to determine the oxygen adatoms migration. Finally, reversible wettability property of graphene due to oxygen adatom migration is demonstrated.